2019
DOI: 10.7762/cnr.2019.8.1.1
|View full text |Cite|
|
Sign up to set email alerts
|

A Vegetables and Fish Dietary Pattern Is Positively Associated with Skeletal Muscle Mass in Korean Men

Abstract: Isolating the effects of a single nutrient or food in relation to health outcomes including increased skeletal muscle mass is a challenging task because dietary constituents are highly correlated and synergistic. Hence, diet pattern analysis may be used to investigate the role of certain diets in health outcomes. The present study investigated the dietary patterns and their relationship to skeletal muscle mass in Korean adults. Data were extracted from the 2008–2011 Korea National Health and Nutrition Examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The Western pattern was positively associated with cancer, especially in females [22]. Although the studies were not related to GC, the Korea National Health and Nutrition Examination Surveys (KNHNES) from 2008 to 2011 observed that a vegetable and fish dietary pattern was positively associated with skeletal muscle mass in Korean men [23]. A systematic review and meta-analysis of the associations of dietary intake with cardiovascular disease in a Korean population summarized that adherence to a healthy dietary pattern (a rice-based or traditional pattern) showed borderline relationships with a decreased risk of elevated total cholesterol and elevated triglycerides [24].…”
Section: Discussionmentioning
confidence: 99%
“…The Western pattern was positively associated with cancer, especially in females [22]. Although the studies were not related to GC, the Korea National Health and Nutrition Examination Surveys (KNHNES) from 2008 to 2011 observed that a vegetable and fish dietary pattern was positively associated with skeletal muscle mass in Korean men [23]. A systematic review and meta-analysis of the associations of dietary intake with cardiovascular disease in a Korean population summarized that adherence to a healthy dietary pattern (a rice-based or traditional pattern) showed borderline relationships with a decreased risk of elevated total cholesterol and elevated triglycerides [24].…”
Section: Discussionmentioning
confidence: 99%
“…Using an absolute cut-off value of ≥ 3 resulted in no overlap in foods with high factor loadings across the identified dietary patterns, which in turn simplified labelling and facilitated interpretation of the dietary patterns. However, an absolute cut-off value of ≥ 2 has also frequently been used to define foods as important contributors to a dietary pattern [ 33 , 40 42 ]. Positive effect estimates for the ‘Western’ and ‘Sweets-focused’ dietary patterns in our study may thus partly be explained by overlap in foods with factor loadings ≥ 2 across the dietary patterns.…”
Section: Discussionmentioning
confidence: 99%